Coupled fixed point theorems for new contractive mixed monotone mappings and applications to integral equations - Işık, H.; Turkoğlu, D. (University of Nis, 2014)
The aim of this paper is to extend the results of Bhaskar and Lakshmikantham and some other authors and to prove some new coupled fixed point theorems for mappings having a mixed monotone property in a complete metric space endowed with a partial order. Our theorems can be used to investigate a large class of nonlinear problems. As an application, we discuss the existence and uniqueness for a solution of a nonlinear integral equation. © 2014, University of Nis. All rights reserved.
Keywords: Contractive condition; Coupled fixed point; Integral equation; Mixed monotone mapping; Partially ordered set